Evaluación del proceso de gestión ambiental de residuos sólidos para la empresa de supermercados Multimart del cantón Pasaje - Polo Baldeón, Jimmy Voltaire (Machala, 2021)
In this integrative project research, we seek to identify the problems generated in the Multimart supermarket, which does not have an environmental management system, which will allow it to implement measures to obtain a better environmental performance in its activities and work functions. In this way, it seeks to benefit and counteract the negative impacts on the environment through the correct management of solid waste. The main objective of this research is to evaluate the process of handling, collection and disposal of solid waste, as well as to determine the type and volume of solid waste. This project consists of 3 chapters, Chapter I details the methodology that has a mixed approach since it involves data collection, as well as qualitative and quantitative analysis in a single study to obtain the results expected to be achieved. It was also considered convenient to use descriptive research since it consists of characterizing a specific situation from the macro to the micro. Exploratory research was used to acquire new data to formulate the research questions, and finally bibliographic research, which is the one that allows obtaining scientific information on the topic addressed. In chapter II, taking into account the results obtained in the previous chapter, the development of an environmental management system based on ISO 14001: 2015 standards is proposed for the Multimart supermarket located in the Pasaje canton of El Oro province, which aims to improve the organizational structure and thus be able to fulfill each of the functions that correspond to them. The environmental management system operates with specific guidelines so that the company can improve its environmental performance and significantly increase its operating efficiency. The environmental management system can also be considered a tool that helps to organize the internal structure that aims to carry out each and every one of the social and environmental requirements. In Chapter III, the feasibility of the proposal was determined using research tools such as the conceptual scheme, which is used to determine the problems and the current state of the supermarket, the avoided cost model aims to quantify the amount that would have to be available to avoid any damage caused to the environment and at the same time the savings that can be generated in the company; the SWOT matrix for the social dimension made it possible to study the strengths, weaknesses, opportunities and threats of the EMS; the PER scheme has as its main objective to know the pressure exerted by the company towards the environment, to know the current situation of the company and to propose environmentally friendly measures. In conclusion, the implementation of the Environmental Management System will serve to significantly improve the organizational structure of the Multimart supermarket, as well as the development of its activities, thus improving its image as a company and the socio-environmental environment in the Pasaje canton of El Oro province. Key words: Solid waste, Environmental management system, Multimart, Environmental impact.
En la presente investigación de proyecto integrador realizada, se busca identificar la problemática que se genera en el supermercado Multimart, el cual no cuenta con un sistema de gestión ambiental, siendo este el que le permitirá implementar medidas para obtener un mejor desempeño ambiental en sus actividades y funciones laborales. De esta manera, se busca beneficiar y contrarrestar los impactos negativos en el medio ambiente mediante el manejo correcto de los residuos sólidos. El objetivo principal de esta investigación es evaluar el proceso de manejo, recolección y disposición de los residuos sólidos, así como determinar el tipo y volumen de los mismos. Este proyecto consta de 3 capítulos, en el capítulo I se detalla la metodología que tiene un enfoque mixto ya que implica la recolección de datos, así como un análisis cualitativo y cuantitativo en un solo estudio para obtener los resultados que se espera conseguir. También se consideró conveniente utilizar la investigación descriptiva ya que esta consiste en caracterizar una situación específica desde lo macro hasta lo micro. Se utilizó la investigación exploratoria para adquirir nuevos datos para formular las preguntas de investigación, y finalmente la investigación bibliográfica, que es la que permite obtener información científica sobre el tema abordado. En el capítulo II, tomando en cuenta los resultados obtenidos en el capítulo anterior, se propone el desarrollo de un sistema de gestión ambiental basado en las normas ISO 14001: 2015 para el supermercado Multimart ubicado en el cantón Pasaje Provincia de El Oro, el cual tiene como objetivo mejorar la estructura organizacional y de esta manera poder cumplir con cada una de las funciones que les corresponde. El sistema de gestión ambiental opera con lineamientos específicos para que la empresa pueda mejorar el desempeño ambiental y a su vez aumentar significativamente su eficiencia operativa. El sistema de gestión medioambiental también puede considerarse una herramienta que ayuda a organizar la estructura interna que tiene como objetivo llevar a cabo todos y cada uno de los requisitos sociales y medioambientales. En el capítulo III, se determinó la viabilidad de la propuesta utilizando herramientas de investigación como el esquema conceptual, que se utiliza para determinar los problemas y el estado actual del supermercado, el modelo de costos evitados pretende cuantificar la suma que habría que disponer para evitar cualquier daño causado al medio ambiente y al mismo tiempo el ahorro que se puede generar en la empresa; la matriz DAFO para la dimensión social permitió estudiar las fortalezas, debilidades, oportunidades y amenazas del SGA; el esquema PER tiene como objetivo fundamental conocer la presión ejercida por la empresa hacia el medio ambiente, conocer la situación actual de la empresa y proponer medidas respetuosas con el medio ambiente. En conclusión, la ejecución del Sistema de Gestión Ambiental servirá para mejorar significativamente la estructura organizacional del supermercado Multimart, así como el desarrollo de sus actividades, mejorando así su imagen como empresa y el entorno socio-ambiental en el cantón Pasaje Provincia de El Oro. Palabras clave: Residuos sólidos, Sistema de gestión ambiental, Multimart, Impacto ambiental.
Keywords: DESECHO SOLIDO; IMPACTO AMBIENTAL; GESTION AMBIENTAL